Implementing tuberculosis preventive therapy: a qualitative study - Apriana, Dina; Nugraheni, Sri Achadi; Suryoputro, Antono (BKM Public Health and Community Medicine, 2025)
Purpose: This study aims to analyze the implementation of tuberculosis preventive therapy (TPT) in Majalengka District using the Van Meter and Van Horn policy implementation model, focusing on inter-organizational communication, resources, implementer disposition, implementing agency characteristics, and economic-socio-political conditions. Methods: This qualitative study employed a case study approach involving six selected community health centers with the highest and lowest TPT coverage. Data were collected through in-depth interviews with six tuberculosis (TB) program managers, five triangulation informants, direct observations, and document reviews. Data were analyzed thematically, involving data reduction, presentation, and inductive conclusion drawing. Results: The study found that communication inconsistencies across national, provincial, and district levels led to information gaps at the community health center level. Implementation was hindered by limited human resources, diagnostic tools, and logistics, as well as the absence of clear internal regulations. However, proactive roles by TB program managers and cadres, supported by community-based outreach strategies, helped mitigate barriers. Social stigma, indirect costs, and low intersectoral coordination remained significant challenges. Conclusion: TPT implementation faced barriers such as inconsistent communication, limited resources, and unclear regulations. Effective TPT implementation requires coordination by the Ministry of Health, improved diagnostics by health facilities, empowerment of health workers and cadres, and strong support from local governments.